SISTEM SAPAAN BAHASA MELAYU RIAU DI SABAK AUH KABUPATEN SIAK SRI INDRAPURA - Ninik Anisyah; Mangatur Sinaga; Hermandra ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This study aimed to describe the system greeting Riau Malay in Sabak Auh Siak Sri Indrapura. The system consisted of greeting greeting kinship and nonkekerabatan. The method used in this study used descriptive qualitative method. Source of research data from multiple informants from Sabak Auh district community. The results of the analysis conducted that the system greeting. Families are the core of eight greeting, greeting the broad family as much as sixteen greeting, greeting in kinship based nicknames as many as four, sapan in kinship based endearment five greeting. In addition nonkekerabatan system based on the age of seven greetings, greetings by the religious title five greetings, greetings by profession seven greeting, the greeting by the nickname of three greetings. The existing system was able to avoid misunderstandings between the user's language, capable of understanding and avoid komplik in the process of greeting greetings.Keywords: Malay, greeting, kinship, nonkekerabatan.